Quantifying RNA modifications by mass spectrometry: a novel source of biomarkers in oncology. (2nd January 2022) - Amalric, Amandine; Bastide, Amandine; Attina, Aurore; Choquet, Armelle; Vialaret, Jerome; Lehmann, Sylvain; David, Alexandre; Hirtz, Christophe
Abstract: Despite significant progress in targeted therapies, cancer recurrence remains a major cause of mortality worldwide. Identification of accurate biomarkers, through molecular profiling in healthy and cancer patient samples, will improve diagnosis and promote personalized medicine. While genetic and epigenetic alterations of DNA are currently exploited as cancer biomarkers, their robustness is limited by tumor heterogeneity. Recently, cancer-associated changes in RNA marks have emerged as a promising source of diagnostic and prognostic biomarkers. RNA epigenetics (also known as epitranscriptomics) is an emerging field in which at least 150 chemical modifications in all types of RNA (mRNA, tRNA, lncRNA, rRNA, and microRNA) have been detected. These modifications fine-tune gene expression in both physiological and pathological processes. A growing number of studies have established links between specific modified nucleoside levels in solid/liquid biopsies, and cancer onset and progression. In this review, we highlight the potential role of epitranscriptomic markers in refining cancer diagnosis and/or prognosis. RNA modification patterns may contain important information for establishing an initial diagnosis, monitoring disease evolution, and predicting response to treatment. Furthermore, recent developments in mass spectrometry allow reliable quantification of RNA marks in solid biopsies and biological fluids. We discuss the great potential of mass spectrometry for identifying epitranscriptomic biomarker signatures in cancer diagnosis. While there are various methods to quantify modified nucleosides, most are unable to detect and quantify more than one type of RNA modification at a time. Mass spectrometry analyses, especially GC-MS/MS and LC-MS/MS, overcome this limitation and simultaneously detect modified nucleosides by multiple reaction monitoring. Indeed, several groups are currently validating mass spectrometry methods that quantify several nucleosides at one time in liquid biopsies. The challenge now is to exploit these powerful analytical tools to establish epitranscriptomic signatures that should open new perspectives in personalized medicine. This review summarizes the growing clinical field of analysis of RNA modifications and discusses pre-analytical and analytical approaches, focusing in particular on the development of new mass spectrometry tools and their clinical applications.